Analysis for Yield Stability of The Promising Cocoa Hybrids at Diverse Agro-climatic Conditions - Agung Wahyu Soesilo (Indonesian Coffee and Cocoa Research Institute, 2011)
Analysis for yield stability on cocoa hybrids has objective to select high yielding hybrid with stable performance throughout the different agro-climatic conditions. These hybrids were crossed between selected clones of TSH 858, KEE 2, KW 162, KW 163 2, KW 165, ICS 13 and NIC 7. Fourteen hybrids were tested with control in a series of multilocation trial at the locations which were classified by altitude and climate differences such as lowland of dry climate in KP Kaliwining, lowland of wet climate in Kalitelepak Plantation, medium highland of wet climate in Jatirono Plantation and medium highland of dry climate in KP Sumber Asin. Trials were established at the randomizedcomplete block design with 4 blocks where in a plot planted 16-24 trees. Yield assessment was evaluated during 4 consecutive years of harvest by counting the number of pods per tree then converted using yield components and bean quality. Stability analysis was performed in linier basis for the yield. The combined analysis of variance performed a significant effect of interaction between hybrid and location within year that means an effect of genotype by environment interaction. Of the tested hybrids, TSH 858 x KEE 2, TSH 858 x KW 162, KW 162 x KEE 2 and the reciprocal performed higher value of the yield than control with deviation to regression (S2di) equal to zero and coefficient of regression (bi) equal to one except for KEE 2 x KW 162 with bi >1. It could be interpreted that those hybrids were stable to perform the yield and well adapted through the locations except for KEE 2 x KW 162 which specifically adapted to the more suitable condition. By respecting to the potency of yield, bean quality and vascular streak dieback resistance, TSH 858 x KW 162 has been released as new hybrid variety and renamed as ICCRI 06H. The hybrid was characterized by the yield potency of 1.99 kg/tree, a dry bean of 1.07 g and fat content of 54.3%. Key words: Stability analysis, yield, Theobroma cacao L., promising hybrids, agro-climatic condition.